GIS-Based Spatial Analysis for Land Suitability and Community Quality of Life Development in Nabire Regency - Yuliawan, Kristia; Pusvita, Ester Ayuk (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study evaluates land suitability in Nabire Regency, Indonesia, employing geographic information systems (GIS) and spatial analysis to enhance community quality of life. Rapid urbanization and increasing land use pressures have resulted in significant environmental challenges, including deforestation, loss of agricultural land, and reduced access to green spaces. By integrating criteria such as land cover, soil quality, water availability, and socio-economic data, the research identifies optimal locations for housing, agriculture, and conservation areas. Results demonstrate disparities in infrastructure and living standards, emphasizing the need for balanced spatial planning. The proposed land suitability map offers actionable insights for policymakers to foster sustainable development, improve resource allocation, and enhance urban and rural livability. This work underscores the critical role of GIS-based spatial analysis in addressing urbanization challenges and guiding equitable development strategies.